2020
DOI: 10.1111/jfbc.13246
|View full text |Cite
|
Sign up to set email alerts
|

Detection and isolation of the typical gut indigenous bacteria from ddY mice fed a casein‐beef tallow‐based or egg yolk‐based diet

Abstract: The effects of whole egg on the cecal microbiome of ddY mice has been reported. To investigate the existence of susceptible indigenous bacteria (SIB) to egg yolks (EY), mice were fed a diet containing either 20% (w/w) milk casein and 17% beef tallow (CT) or 12% milk casein and 27% EY for 14 days, and then, the cecal microbiome was analyzed by 16S rRNA (V4) amplicon sequencing. To isolate the typical species in each diet group, culture‐dependent viable bacterial counts were determined on Blood Liver (BL) and Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Frozen stock cultures were melted and spread onto Gifu Anaerobic Medium (GAM) agar plates (Nissui, Tokyo, Japan) under anaerobic conditions using an Anaeropack (Mitsubishi, Tokyo, Japan); Fukunaga et al demonstrated that GAM medium is sufficient for culturing F. rodentium. 21,22 A single colony was picked and added to 3.5 mL of autoclaved GAM bouillon medium in a 4 mL vial and incubated at 37 °C overnight. Aliquots (20 μL) of the subsequent bacterial culture were further divided into 3.5 mL starch-free semi-solid agar GAM medium (Nissui) with or without soluble OF at the indicated concentrations and then cultured at 37 °C overnight in accordance with our previous study.…”
Section: Anaerobic Culture For Faecalibaculum Rodentium and Holdemane...mentioning
confidence: 99%
“…Frozen stock cultures were melted and spread onto Gifu Anaerobic Medium (GAM) agar plates (Nissui, Tokyo, Japan) under anaerobic conditions using an Anaeropack (Mitsubishi, Tokyo, Japan); Fukunaga et al demonstrated that GAM medium is sufficient for culturing F. rodentium. 21,22 A single colony was picked and added to 3.5 mL of autoclaved GAM bouillon medium in a 4 mL vial and incubated at 37 °C overnight. Aliquots (20 μL) of the subsequent bacterial culture were further divided into 3.5 mL starch-free semi-solid agar GAM medium (Nissui) with or without soluble OF at the indicated concentrations and then cultured at 37 °C overnight in accordance with our previous study.…”
Section: Anaerobic Culture For Faecalibaculum Rodentium and Holdemane...mentioning
confidence: 99%
“…In addition, Lachnospiraceae and Ruminococcaceae were significantly reduced at the family level, and Erysipelotrichaceae was significantly increased. At the genus level, Parasutterella and Coprostanoligenes showed a relatively high abundance ( Fukunaga et al, 2020 ). Parasutterella has been defined as a core component of the human and mouse gut microbiota and has been correlated with bile acid maintenance and cholesterol metabolism ( Ju et al., 2019 ).…”
Section: Effects Of Egg Products and Egg Protein On The Gut Microbiotamentioning
confidence: 99%